SOSIALISASI UPAYA UNTUK MENINGKATKAN LITERASI BANK SYARIAH DI MASYARAKAT PERDESAAN - Wina Sari Asmara; Raden Hebat Kurnia; Alfi Rochmi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The level of Sharia financial literacy in rural Indonesian communities remains low, leading to minimal utilization of Sharia banking products and services despite their significant potential. This community service initiative aims to enhance Sharia bank literacy among rural communities through comprehensive socialization activities.Implementation methods included an initial survey, interactive outreach on fundamental concepts, principles, and Sharia banking products like Murabahah, Mudharabah, and Ijarah, followed by discussions and distribution of educational materials. The activity results demonstrated a significant increase in community understanding of Sharia banking, evidenced by post-test outcomes and participant enthusiasm.This socialization successfully corrected misconceptions and fostered community interest in utilizing Sharia bank products. In conclusion, this activity effectively improved Sharia banking literacy, which is expected to encourage community participation in the Sharia economy and contribute to rural welfare improvement. Recommendations include sustainable programs, collaboration with local Sharia banks, and the development of more diverse educational materials.